Advanced Material Engineering to Tailor Nucleation and Growth towards Uniform Deposition for Anode‐Less Lithium Metal Batteries. Issue 50 (1st November 2022) - Qian, Lanting; Zheng, Yun; Or, Tyler; Park, Hey Woong; Gao, Rui; Park, Moon; Ma, Qianyi; Luo, Dan; Yu, Aiping; Chen, Zhongwei
Abstract: Anode‐less lithium metal batteries (ALMBs), whether employing liquid or solid electrolytes, have significant advantages such as lowered costs and increased energy density over lithium metal batteries (LMBs). Among many issues, dendrite growth and non‐uniform plating which results in poor coulombic efficiency are the key issues that viciously decrease the longevity of the ALMBs. As a result, lowering the nucleation barrier and facilitating lithium growth towards uniform plating is even more critical in ALMBs. While extensive reviews have focused to describe strategies to achieve high performance in LMBs and ALMBs, this review focuses on strategies designed to directly facilitate nucleation and growth of dendrite‐free ALMBs. The review begins with a discussion of the primary components of ALMBs, followed by a brief theoretical analysis of the nucleation and growth mechanism for ALMBs. The review then emphasizes key examples for each strategy in order to highlight the mechanisms and rationale that facilitate lithium plating. By comparing the structure and mechanisms of key materials, the review discusses their benefits and drawbacks. Finally, major trends and key findings are summarized, as well as an outlook on the scientific and economic gaps in ALMBs. Abstract : Schematic representation of strategies and materials associated with lowering nucleation barrier toward uniform plating for anodeless lithium metal batteries by means of SEI protection, increasing lithiophilicity of the surface, and increasing nucleation sites on the anode surface.